2020
DOI: 10.1039/d0dt00904k
|View full text |Cite
|
Sign up to set email alerts
|

Structural and metal–halogen exchange reactivity studies of sodium magnesiate biphenolate complexes

Abstract: Sodium magnesiates incorporating the (rac)-BIPHEN ligand have been prepared and characterised and subsequently used in metal–halogen exchange reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…This was imperative to assess if these complexes exist as the sole compounds in solution or if alternatively they are in equilibrium with other organometallic species as previously shown for related lithium magnesiates [LiMg s Bu 2 (OR’)] (R’=2‐ethylhexyl) (Figure 1b) [15] . Related to these findings, O'Hara has also reported that heteroleptic alkali metal magnesiates [(rac)BIPHEN]M 2 Mg n Bu 2 (THF) 4 (M=Li or Na), containing the bis(aryloxide) group BIPHEN (BIPHEN=5,5’,6,6’‐tetramethyl‐3,3’‐di‐tert‐butyl‐1,1’‐biphenyl‐2,2’‐diol) undergo a redistribution process in THF solution to form homoleptic alkoxy [(rac)BIPHEN] 2 M 2 Mg(THF) 4 and alkyl rich magnesiate [M 2 Mg n Bu 4 (THF) 4 ] [49,50] . Interestingly, for 1 – 3 , the presence of the tridentate alkoxide ligand seems to impose a greater stability of these bimetallic species in solution as no evidence of ligand redistribution and formation of other organometallic compounds in solution were observed.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…This was imperative to assess if these complexes exist as the sole compounds in solution or if alternatively they are in equilibrium with other organometallic species as previously shown for related lithium magnesiates [LiMg s Bu 2 (OR’)] (R’=2‐ethylhexyl) (Figure 1b) [15] . Related to these findings, O'Hara has also reported that heteroleptic alkali metal magnesiates [(rac)BIPHEN]M 2 Mg n Bu 2 (THF) 4 (M=Li or Na), containing the bis(aryloxide) group BIPHEN (BIPHEN=5,5’,6,6’‐tetramethyl‐3,3’‐di‐tert‐butyl‐1,1’‐biphenyl‐2,2’‐diol) undergo a redistribution process in THF solution to form homoleptic alkoxy [(rac)BIPHEN] 2 M 2 Mg(THF) 4 and alkyl rich magnesiate [M 2 Mg n Bu 4 (THF) 4 ] [49,50] . Interestingly, for 1 – 3 , the presence of the tridentate alkoxide ligand seems to impose a greater stability of these bimetallic species in solution as no evidence of ligand redistribution and formation of other organometallic compounds in solution were observed.…”
Section: Resultsmentioning
confidence: 78%
“… [15] Related to these findings, O'Hara has also reported that heteroleptic alkali metal magnesiates [(rac)BIPHEN]M 2 Mg n Bu 2 (THF) 4 (M=Li or Na), containing the bis(aryloxide) group BIPHEN (BIPHEN=5,5’,6,6’‐tetramethyl‐3,3’‐di‐tert‐butyl‐1,1’‐biphenyl‐2,2’‐diol) undergo a redistribution process in THF solution to form homoleptic alkoxy [(rac)BIPHEN] 2 M 2 Mg(THF) 4 and alkyl rich magnesiate [M 2 Mg n Bu 4 (THF) 4 ]. [ 49 , 50 ] Interestingly, for 1 – 3 , the presence of the tridentate alkoxide ligand seems to impose a greater stability of these bimetallic species in solution as no evidence of ligand redistribution and formation of other organometallic compounds in solution were observed. This was supported by 1 H‐DOSY NMR spectroscopic studies which indicated that in all cases a single molecular entity is formed containing both alkyl and alkoxide groups (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synergic behavior arising from the chemical cooperativity of two different metal species allows transformations to be per-formed that would be unachievable using conventional monometallic reagents. Most reported systems are based on alkyl/ aryl, 4,5 or amido 6 alkali metal magnesiates, which were applicable for magnesium-halogen exchange of aryl substrates, 7 enantioselective alkylation of aldehydes, 8 cyclization of alkynols, 9 transfer hydrogenation of alkenes, 10 or hydroamination of alkynes and alkenes. 11 In organic synthesis, very important synergistic heterobimetallic reagents were alkyl or amido alkali metal-magnesium halides, so-called turbo-Grignard or turbo-Hauser bases.…”
Section: Introductionmentioning
confidence: 99%
“…[18, 19b, 21] iPrMgCl•LiClh as also shown great functional group tolerance under mild reaction conditions as well as delivering high levels of chemoselectivity.R ecently we have reported the first examples of metal-halogen exchange using bimetallic sodium-magnesiates which incorporate chiralp henoxide ligands. [22] Zn-halogen exchange reactions of aromatic halides have also been investigated to prepare arylzincc ompounds, which can then be used, for instance, in Negishi cross-coupling transformations. [23] The CÀZn bond is relativelyc ovalenta nd tolerates most of the functionalg roups;h owever,t he less polar dialkylzinc compounds used requirea dditives, such as Li(acac), (acac is acetylacetonate)f or the Zn/I-exchange reaction to occur effectively.A ni mportant example was published by Hevia, based on am agnesium tris(tert-butyl) zincate reagent, that efficiently promotes Zn/I-exchange reactions of different functionalized aromatic halidesi nT HF,a voiding the use of additives and in a high atom economic exchange process.…”
Section: Introductionmentioning
confidence: 99%